Analyzing the impact of asymmetric shocks on the interaction strategies between the monetary authorities of two countries - Леонид Серков (Вестник Пермского университета: Серия Экономика)
Introduction. Stronger interdependence of countries driven by the international trade gives rise to a relevant question whether there is a need for each country to pursue its independent monetary policies or whether it is advisable to coordinate these policies. In other words, the question of whether we should consider the benefits from harmonizing international monetary policies becomes a key issue in the debate about the appropriate monetary policy strategies in open economies. Purpose. The objective of this study is to analyze the impact of asymmetric aggregate demand shocks on the need for monetary policy coordination in a simple stochastic model of two interacting countries. Materials and Methods. The authors analyze the equilibrium states of the examined interaction strategies between the monetary authorities with an analytical method by minimizing the loss function and solving sequential statistical problems of optimization. Results. The equilibrium states of the macroeconomies for interacting countries have been looked at when the monetary policies are coordinated and when they are not coordinated (the Nash and Stackelberg equilibrium) under asymmetric serially uncorrelated demand shocks. The response of inflation to asymmetric demand shocks is proven to be less for the Nash coordinated policy than for non-coordinated policy. This is opposite to the result obtained under symmetric supply shocks. The loss function analysis shows that the compensation of demand shocks is found to be more costly in the Nash equilibrium than under the coordination policy practiced by monetary authorities. The analysis of the monetary authorities’ interaction strategies showed that the real exchange rate plays an important role in balancing supply and demand in the two economies. Conclusions. The key finding of the study is that asymmetric shocks affect the evaluation of interaction strategies practiced by monetary authorities. The practical significance of the results lies in the fact that monetary authorities could stabilize the economy by creating buffers against external shocks.